2019
DOI: 10.1590/0104-1428.06119
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and analysis of the parietal polysaccharides of acorn pericarps from Quercus trees

Abstract: Acorns produced by Quercus trees are currently underexploited and undervalued. To evaluate the commercial and health benefits of acorns, we examined the cell wall components of acorn pericarps from Quercus suber and Quercus ilex, growing in NorthWestern Algeria. Acorn pericarps were sequentially extracted and the polysaccharide fractions were analyzed by gas liquid chromatography and Fourier-transform infrared spectroscopy. The lignocellulosic fraction was the major component of Q. suber and Q. ilex cell walls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…bonds present in polysaccharide structures [33], [35] 1050 (sharp band) -C-O-C-ether linkage of pectin [1], [36] 830 (weak, sharp peak) Hydrogen-bonded O-H out-of-plane bending [33] MNT-nAg/AMT-nAg 3345/3363 (intense, very broad band)…”
Section: Vibrations Of the -C-o-c-and -C-o-hmentioning
confidence: 99%
“…bonds present in polysaccharide structures [33], [35] 1050 (sharp band) -C-O-C-ether linkage of pectin [1], [36] 830 (weak, sharp peak) Hydrogen-bonded O-H out-of-plane bending [33] MNT-nAg/AMT-nAg 3345/3363 (intense, very broad band)…”
Section: Vibrations Of the -C-o-c-and -C-o-hmentioning
confidence: 99%
“…In addition, our results clearly showed that among seven Fagaceae species, there was a significantly negative correlation between concentration of the total phenolics and the thickness of the pericarp, suggesting a trade‐off between chemical and physical defense. Formation of physical defense is related to the high lignification of the pericarp, and the phenolic substances are a precursor substance of lignin (Caretto et al, 2015; Lattanzio et al, 2006; Mébarki et al, 2019). Therefore, the trade‐off between physical and chemical defenses suggests that the total amount of C that could be invested into defense is limited.…”
Section: Discussionmentioning
confidence: 99%